Protocol design for the UAV-aided satellite network - Ong, Wei Xiang (2018)
The satellite communication has served a vital role in today’s world of wireless communications. Users can transmit their information such as video, voice and data over the space through the means of satellite. One of the major drawbacks is the large distance between the users on Earth and geo-stationary satellite. This results in poor received signal level which affects the quality of the transmitted message. There is absence in control of the mobility of satellite as the position of the geo-stationary satellite is fixed, and the position of the user terminals are arbitrary. As such, a High-Altitude Pseudo-Satellite (HAPS) is introduced as a relay for optimal control and configuration to ensure signals are transmitted with minimized error. The HAPS is nothing but an Unmanned Aerial Vehicle (UAV). In this dissertation, the decoder techniques being simulated and tested for bit-error rate (BER) performance in relay-aided SATCOM are Zero Forcing, Minimum Mean Square Error, Maximal Ratio Combining and Optimum Combining. The first two schemes are further expanded with Successive Interference Cancellation with Optimal Ordering. The optimisation of UAV positioning is also being studied to effectively decode and forward transmissions with lower BER. Realistic and measurable data is used in the computations, and the simulations are done with MATLAB software.